MicroRNA detection in biologically relevant media using a split aptamer platform. (1st September 2022) - Wang, Liming; Hast, Kern; Aggarwal, Tushar; Baci, Melih; Hong, Jonathan; Izgu, Enver Cagri
Graphical abstract: Abstract: MicroRNA (miRNA)-based intercellular communication has been implicated in many functional and dysfunctional biological processes. This has raised interest in the potential use of miRNAs as biomarkers for diagnosis and prognosis. Though the list of clinically significant miRNA biomarkers is expanding, it remains challenging to adapt current chemical tools to investigate miRNAs in complex environments native to cells and tissues. We describe here a methodology for rapidly developing aptamer-based fluorescent biosensors that can specifically detect miRNAs in biologically relevant media (10–30% v/v), including medium collected from cultured HeLa cells, human serum, and human plasma. This methodology involves the semi-rational design of the hybridization between DNA oligonucleotides and the miRNA target to build a pool of potential aptamers, and the screening of this pool for high signal-to-background ratio and target specificity. The DNA oligonucleotides are readily available and require no chemical modification, rendering these chemical tools highly adaptable to any novel and niche miRNA target. Following this approach, we developed sensors that detect distinct oncogenic miRNA targets (miR-19b, miR-21, and miR-92a) at concentrations as low as 5 nM without amplification and are selective against single-nucleotide mutants. This work provides a systematic approach toward the development of miRNA biosensors that are easily accessible and can perform in biological environments with minimal sample handling.